2020
DOI: 10.1002/trtr.1885
|View full text |Cite
|
Sign up to set email alerts
|

Debugging the Writing Process: Lessons From a Comparison of Students’ Coding and Writing Practices

Abstract: This study of three young students' compositional activities explores how coding can support the teaching of writing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Finally, it is possible that the language system may play a role in learning to program ( Prat et al, 2020 ), even if it is not required to support code comprehension once the skill is learned. Studies advocating the ‘coding as another language’ approach ( Bers, 2019 ; Bers, 2018 ; Sullivan and Bers, 2019 ) have found that treating coding as a meaning-making activity rather than merely a problem-solving skill had a positive impact on both teaching and learning to program in the classroom ( Hassenfeld et al, 2020 ; Hassenfeld and Bers, 2020 ). Such results indicate that the language system and/or the general semantic system might play a role in learning to process computer code, especially in children, when the language system is still developing.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is possible that the language system may play a role in learning to program ( Prat et al, 2020 ), even if it is not required to support code comprehension once the skill is learned. Studies advocating the ‘coding as another language’ approach ( Bers, 2019 ; Bers, 2018 ; Sullivan and Bers, 2019 ) have found that treating coding as a meaning-making activity rather than merely a problem-solving skill had a positive impact on both teaching and learning to program in the classroom ( Hassenfeld et al, 2020 ; Hassenfeld and Bers, 2020 ). Such results indicate that the language system and/or the general semantic system might play a role in learning to process computer code, especially in children, when the language system is still developing.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that students from all literacy levels were able to master an introductory programming language, albeit, with varying levels of ease, can be leveraged for the development of literacy. Recent research (Hassenfeld & Bers, 2020;Thompson, Tanimoto, Berninger, & Nagy, 2016) has shown how programming composition can support young students in writing composition. Specifically, facility and comfort with debugging can help students with the cognitively and conceptually difficult work of revision in writing and enhance their motivation to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hassenfeld and Bers (2020) posited the connection between reading and writing should be extended to the composing processes of programming as well. Vee (2017) argued the practice of programming bears significant similarities to writing because of its affordances for information creation, organization and dissemination.…”
Section: Programming-as-writingmentioning
confidence: 99%
“…Enhanced ability to view compositions from an audience perspective expands the ability to make deliberate design choices to increase audience engagement. Hassenfeld and Bers (2020) discovered students had a greater willingness to revise their computer programs than their written compositions because of easier identification with the audience. Students were able to see what was missing when viewing their programs, which informed their revising/reprogramming process.…”
Section: Supportive Structures In Scratchmentioning
confidence: 99%
See 1 more Smart Citation